Paisagem iluminada em áreas urbanas patrimoniais : experimentação metodológica no sítio histórico de Santa Leopoldina-ES - Favero, Cassio Santana (2018)
Cultural landscapes and artificial lighting are, nowadays, two architectural themes that contribute for the scenery of preservation of cultural and historical architectural urban landmarks. In the cities, the care with the night time originate a new kind